Factores asociados al embarazo ectópico según la percepción de los estudiantes de Enfermería de la Universidad Nacional de Loja - Sarango Cumbicus, Dennisse Astrid (2019)
Ectopic Pregnancy is a major public health problem, as it is one of the leading causes of maternal death. The present study entitled “Factors associated with Ectopic Pregnancy according to the perception of Nursing students of the National University of Loja”, had as a general objective to identify the perception of the risk factors associated with Ectopic Pregnancy in Nursing students of the University Nacional de Loja during the school period October 2018 - March 2019. This study was descriptive-cross-sectional, with a sample of 146 people, to whom a survey was applied. The results were that in a large proportion, their place of origin is the Loja province, of single civil status, the female sex predominates and the average age is 24.2 years. Among the risk factors associated with ectopic pregnancy, according to the participants' perception were: infertility, vaginal showers, race, fertility techniques, gynecological and abdominal surgeries, previous pelvic inflammatory disease, age of first intercourse, sexual promiscuity, infections of sexual transmission, tobacco and alcohol. Regarding the protective factors, according to the perspective of those involved, they were to avoid: having vaginal showers, sexual promiscuity, smoking and the use of condoms to contract sexually transmitted infections. It could be concluded that the majority of the students surveyed have perception, or knowledge, about the factors associated with ectopic pregnancy. Keywords: Knowledge, senses, students, pregnancy, risk, protectors.